L’appropriation ludique de la forêt au Québec : d’une gestion privée de « club » à une intervention publique de protection (1885-1935) - Serge Gagnon (Études Caribéennes)
The large natural areas, linked to the various resorts, were custodians of the best trout lakes, huge areas of waterfowl, deer of Virginia and a large number of salmon rivers. If the coast and the mountains acted as attractors in the case of the holiday, it was different for the club hunting and fishing, which have emerged in the mid-nineteenth century and have increased from 1885. In this case, the mechanics at work seems to have raised the "great outdoors" as a territorial and "rider of the woods" as emblematic figure of the romantic hero. In this case, the mechanics at work seems to have raised the "great outdoors" as a territorial and "rider of the woods" as emblematic figure of the romantic hero. The argument developed in this article will seek to show that tourism and vacationing were in Quebec recovery procedures such as positional geo-anthropological. The “clubage” Laurentian, in the broadest sense, will be formed in this sense the assumption of internal colonization. Whether Lake Saint-Jean, Mauricie and Laurentides in general, we find the effectiveness of the structural pathways of human settlement geography developed structural: the occupation of territory utility presupposes not available not primarily a transformation of nature but a recovery of vague ... by the tourism and the holiday resort.